Lessons from the 20 Years of the Brazilian Inflation Targeting Regime - Araujo, Eliane; Arestis, Philip (Panoeconomicus, 2019)
This paper analyzes the Brazilian experience with the Inflation Targeting Regime (ITR) since its adoption in June 1999. The theoretical analysis starts by covering the New Consensus Macroeconomics (NCM) only policy, in which the ITR is the monetary policy recommendation. This discussion is then complemented first by the current debate in the international mainstream on the need for a flexible ITR that considers the effects of monetary policy on the economy and second by the heterodox discussion on the need to completely abandon the ITR. The discussion on the Brazilian experience and its comparison with international experiences show that Brazil is one of the few countries where the monetary policy objective is restricted to price control and where the horizon for returning inflation to the target is only one year. Within this institutional framework, the Brazilian economy under the ITR is marked by the maintenance of extremely high real and nominal interest rates and with difficulties in meeting the inflation targets. The price control obtained also did not generate the expected externalities in terms of economic growth and employment. After almost 20 years of adopting the ITR in Brazil, it has generated exaggerated contractionary pressures on the Brazilian economy, indicating the need for a thorough examination of monetary institutions in Brazil in order to resume economic growth with price stability and social equity. Key words: Inflation targeting, Brazilian experience, Contractionary effects, Price stability, Social equity. JEL: E06, E12, E42. Lekcije nakon 20 godina režima ciljanja inflacije u Brazilu U radu je analizirano iskustvo Brazila sa režimom ciljanja inflacije (ITR) od njegovog usvajanja u junu 1999. godine. Teorijska analiza počinje tako što pokriva novi makroekonomski konsenzus (NCM), jedine politike u kojoj je ITR preporuka monetarne politike. Diskusija se prvo nadopunjuje aktuelnom debatom u međunarodnom mainstream-u o potrebi za fleksibilnim ITR-om koja razmatra efekte monetarne politike na ekonomiju, a zatim heterodoksnom diskusijom o potrebi potpunog napuštanja ITR-a. Rasprava o iskustvu Brazila i njegovo poređenje sa međunarodnim iskustvima pokazuje da je Brazil jedna od retkih zemalja u kojoj je cilj monetarne politike ograničen na kontrolu cena i gde je period za vraćanje inflacije na ciljani nivo samo godinu dana. U okviru ovog institucionalnog okvira, brazilska ekonomija pod ITR-om je obeležena održavanjem izuzetno visokih realnih i nominalnih kamatnih stopa i teškoćama u ispunjavanju ciljeva inflacije. Primena kontrole cena takođe nije generisala očekivane eksternalije u smislu ekonomskog rasta i zaposlenosti. Nakon skoro 20 godina od uvođenja ITR-a u Brazilu, došlo je do prekomernog pritiska na brazilsku ekonomiju, što ukazuje na potrebu za temeljnim ispitivanjem monetarnih institucija Brazila kako bi se nastavio ekonomski rast uz stabilnost cena i socijalnu jednakost. Ključne reči: Targetiranje inflacije, iskustvo Brazila, kontrakcioni efekti, cenovna stabilnost, socijalna jednakost.